Mandatory and voluntary disclosures of Serbian listed companies: Achieved level and some recommendation for improving their relevance - Ksenija Denčić-Mihajlov; Dejan Spasić (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2016)
Purpose - This paper investigates mandatory and voluntary disclosure practices of non-financial listed companies on the Belgrade Stock Exchange. The results help in determining the level of transparency of Serbian s listed companies and in formulating recommendations for improving the quality and relevance of disclosed information. Design/methodology/approach - We focus on modeling both mandatory and voluntary disclosure indices for financial and non-financial information in order to evaluate the level of disclosure of 63 Serbian companies for reporting period 2012. Findings - We found the low level of both mandatory and voluntary disclosures. Concerning mandatary disclosure, the information that is least frequently disclosed by the sample companies are those related to the material content of the financial statements (information on changes in accounting estimates and corrections of fundamental errors in the previous period, as well as related companies). Serbian companies usually disclose information that contributes to their greater visibility. Similar to the mandatory disclosure, usually published voluntary information are mostly "neutral" from the point of impact on the values reported in the financial statements, which do not contribute to a better understanding of the financial position, profitability and cash flows of the company. Research limitations/implications - There is a limitation concerning the sample size (which is generally intrinsic to Serbian capital market size) and the sample structure (research is limited to listed non-financial companies). The study covers the annual reports for 2012 which in Serbia coincides with a crisis period. The same research methodology could be applied on a larger and comprehensive database (non-listed companies) and include period after 2012, which will allow the analysis of evolution of disclosure practices by companies within new accounting framework. Originality/value - The authors give some recommendations for improving the relevance of financial and non-financial disclosures in order to increase the efficiency of capital markets.
Keywords: M41; 330; disclosure index; financial and non-financial information; capital market; transparency; recommendation